An assessment of terminology for intraspecific diversity in fishes, with a focus on “ecotypes” and “life histories” - Benjamin J. Clemens; Carl B. Schreck (Ecology and Evolution, 2021)
Abstract Understanding and preserving intraspecific diversity (ISD) is important for species conservation. However, ISD units do not have taxonomic standards and are not universally recognized. The terminology used to describe ISD is varied and often used ambiguously. We compared definitions of terms used to describe ISD with use in recent studies of three fish taxa: sticklebacks (Gasterosteidae), Pacific salmon and trout (Oncorhynchus spp., “PST”), and lampreys (Petromyzontiformes). Life history describes the phenotypic responses of organisms to environments and includes biological parameters that affect population growth or decline. Life‐history pathway(s) are the result of different organismal routes of development that can result in different life histories. These terms can be used to describe recognizable life‐history traits. Life history is generally used in organismal‐ and ecology‐based journals. The terms paired species/species pairs have been used to describe two different phenotypes, whereas in some species and situations a continuum of phenotypes may be expressed. Our review revealed overlapping definitions for race and subspecies, and subspecies and ecotypes. Ecotypes are genotypic adaptations to particular environments, and this term is often used in genetic‐ and evolution‐based journals. “Satellite species” is used for situations in which a parasitic lamprey yields two or more derived, nonparasitic lamprey species. Designatable Units, Evolutionary Significant Units (ESUs), and Distinct Population Segments (DPS) are used by some governments to classify ISD of vertebrate species within distinct and evolutionary significant criteria. In situations where the genetic or life‐history components of ISD are not well understood, a conservative approach would be to call them phenotypes.